Comparative Profiling of Serum Protein Biomarkers in Rheumatoid Arthritis–Associated Interstitial Lung Disease and Idiopathic Pulmonary Fibrosis. Issue 3 (5th February 2020) - Kass, Daniel J.; Nouraie, Mehdi; Glassberg, Marilyn K.; Ramreddy, Nitya; Fernandez, Karen; Harlow, Lisa; Zhang, Yingze; Chen, Jean; Kerr, Gail S.; Reimold, Andreas M.; England, Bryant R.; Mikuls, Ted R.; et al.
Abstract : Objective: Interstitial lung disease (ILD) is a frequent complication of rheumatoid arthritis (RA), occurring in up to 40% of patients during the course of their disease. Early diagnosis is critical, particularly given the shared clinicoepidemiologic features between advanced rheumatoid arthritis–associated ILD (RA‐ILD) and idiopathic pulmonary fibrosis (IPF). This study was undertaken to define the molecular basis of this overlap through comparative profiling of serum proteins in RA‐ILD and IPF. Methods: Multiplex enzyme‐linked immunosorbent assays (ELISAs) were used to profile 45 protein biomarkers encompassing cytokines/chemokines, growth factors, and matrix metalloproteinases (MMPs) in sera obtained from RA patients with ILD and those without, individuals with IPF, and healthy controls. Levels of selected serum proteins were compared between patient subgroups using adjusted linear regression, principal component analysis (PCA), and least absolute shrinkage and selection operator (LASSO) modeling. Results: Multiplex ELISA‐based assessment of sera from 2 independent cohorts (Veterans Affairs [VA] and Non‐VA) revealed a number of non‐overlapping biomarkers distinguishing RA‐ILD from RA without ILD (RA–no ILD) in adjusted regression models. Parallel analysis of sera from IPF patients also yielded a discriminatory panel of protein markers in models adjusted for age/sex/smoking, which showed differential overlap with profiles linked to RA‐ILD in the VA cohort versus the Non‐VA cohort. PCA revealed several distinct functional groups of RA‐ILD–associated markers that, in the VA cohort, encompassed proinflammatory cytokines/chemokines as well as 2 different subsets of MMPs. Finally, LASSO regression modeling in the Non‐VA and VA cohorts revealed distinct biomarker combinations capable of discriminating RA‐ILD from RA–no ILD. Conclusion: Comparative serum protein biomarker profiling represents a viable method for distinguishing RA‐ILD from RA–no ILD and identifying population‐specific mediators shared with IPF.